2021
DOI: 10.3390/ijerph182010854
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Running Velocity during the 30–15 Intermittent Fitness Test Using Accelerometry-Derived Metrics and Physiological Parameters: A Machine Learning Approach

Abstract: Measuring exercise variables is one of the most important points to consider to maximize physiological adaptations. High-intensity interval training (HIIT) is a useful method to improve both cardiovascular and neuromuscular performance. The 30–15IFT is a field test reflecting the effort elicited by HIIT, and the final velocity reached in the test is used to set the intensity of HIIT during the training session. In order to have a valid measure of the velocity during training, devices such as GPS can be used. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…By increasing the sample size, it may be possible to obtain more precise results and to test more intricate machines, such as deep learning. However, it has been showed that ML approaches similar to those used in this study can provide very highly accurate estimations of physiological and performance parameters, and that they are superior to univariate methods [ 62 , 63 ]. Nevertheless, the proposed model was developed using a cross-validation procedure, thereby ensuring its generalization performance.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the sample size, it may be possible to obtain more precise results and to test more intricate machines, such as deep learning. However, it has been showed that ML approaches similar to those used in this study can provide very highly accurate estimations of physiological and performance parameters, and that they are superior to univariate methods [ 62 , 63 ]. Nevertheless, the proposed model was developed using a cross-validation procedure, thereby ensuring its generalization performance.…”
Section: Discussionmentioning
confidence: 99%
“…The training was performed using nested cross-validation (nCV), where the dataset is divided into folds, and the model is trained repeatedly on all but one fold of the data. The inner loop determines the most effective hyperparameters via validation, while the outer loop assesses the model’s performance over iterations through testing [ 32 , 33 , 34 ]. Specifically, 5-fold cross validation was implemented.…”
Section: Methodsmentioning
confidence: 99%
“…An SVR approach was used as previously described ( 44 ). In this case, the SVR-based models with linear kernel were developed to predict the different HRV metrics [i.e., mean HR (beats/min), mean RR (ms), LF/HF, SDDN (ms), RMSSD (ms), pNN50 (%), and TINN (ms)] evaluated from the PPG signals.…”
Section: Methodsmentioning
confidence: 99%